Lyssaviruses in Insectivorous Bats, South Africa, 2003–2018 - Coertse, Jessica; Grobler, Colyn S.; Sabeta, Claude T.; Seamark, Ernest C.J.; Kearney, Teresa; Paweska, Janusz T.; Markotter, Wanda (Emerging infectious diseases, 2020)
We detected 3 lyssaviruses in insectivorous bats sampled in South Africa during 2003-2018. We used phylogenetic analysis to identify Duvenhage lyssavirus and a potentially new lyssavirus, provisionally named Matlo bat lyssavirus, that is related to West Caucasian bat virus. These new detections highlight that much about lyssaviruses remains unknown.